(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
This essay aims to identify how knowledge is grounded in an organization, ie as from a series of theoretical postulates, they become paradigms to promote learning from the construction and transformation of business models focused on Knowledge management also like these individual and collective expertise interact to innovate and transfer ideas to build networks of discernment, also supported the use of technology. The methodology for this study was the literature review and expert literature. The results show a series of theoretical reflections that contribute to spread hope and dimension of knowledge management in organizations. Also, indicated that the management of knowledge through innovative policies conducive to business success generating sources of competitive advantage. Therefore, we conclude that an organization and its members must always be ready to test their paradigms, their knowledge, ideas and concepts, and proceeded to systematically exclude those that are no longer useful for the competitive performance of the company, which strategically link ensures the stability and growth in the context of learning organizations.